Pemberdayaan Masyarakat Pengrajin Batu Bata Merah Dikelurahan Kayumalue Ngapa Kecamatan Palu Utara Kota Palu Sulawesi Tengah - Putri Dwi Kurniati; Mardafila Mardafila; Nicky Cintya; Mirani Juniar; Asni Asni; Faqihul Hayat Darma Putra; Abd. Wahid Idris T. Yutu (Lembaga Pengembangan Kinerja Dosen, 2025)
The aim of the service is to find out how the sub-district government is making efforts to empower the community of brick craftsmen in Kayumalue Ngapa Subdistrict, North Palu District, Palu City. Community Empowerment is an activity to increase community participation in accessing and enjoying a better and more decent life so that they experience increased capacity and social protection. This activity is carried out through community service, which is a community service-based activity to increase students' sense of empathy for the conditions of society and their environment. community service was carried out in North Palu District, Kaymalue Ngapa Village, with the results of this service showing that efforts to empower the community's economy through the red brick industrial center are an effort to utilize natural resources in Kaymalue Ngapa Village. The implementation is a craft activity that utilizes human resources. By empowering the community's economy through the red brick industrial center, it can increase the community's economic income. The existence of a red brick industrial center creates jobs for the community thereby increasing the community's economic income. The increase in income from working in the red brick industry can be seen from the income one earns. His income is sufficient to meet basic needs and basic needs.